Review of Nanocoatings for Building Application - Boostani, Haleh; Modirrousta, Sama (Elsevier Science Bv, 2016)
Nanocoatings are regarded as the most promising high-performance materials for construction applications. Thanks to their self-assembly effect, they represent remarkable characteristics against environmental agents compared to conventional coating materials in construction industry. They also show high performance in contradiction of energy efficiency, CO2 emission, and the air quality improvement. In this study, a review of nanocoatings on the basic reaction mechanisms and materials, in general, and for building application, in particular, is presented. (C) 2015 The Authors. Published by Elsevier Ltd.
International Conference on Sustainable Design, Engineering and Construction (ICSDEC) -- MAY 18-20, 2016 -- Arizona State Univ, Coll Avenue Commons, Tempe, AZ
Keywords: Building industry; Nanocoatings; Nanomaterials; Self-assembly; Sustainable development